RANCANG BANGUN SISTEM AKUARIUM CERDAS UNTUK PENGENDALIAN KUALITAS HIDUP IKAN GABUS BERBASIS INTERNET OF THINGS - Valeri, Rayhan Azhar; Maulana, Eka; Kusmaryanto, Sigit (Jurnal Mahasiswa TEUB, 2025)
This study presents the design and implementationof a smart aquarium system based on the Internet of Things(IoT) to optimize the growth performance of snakehead fish(Channa striata) through environmental control. The systemutilizes an ESP32 microcontroller connected to a DS18B20temperature sensor, PH-4502C pH sensor, and actuatorsincluding a water heater, dosing pumps, and an automatedfeeding system using LDR and servo. Temperature regulationis managed using a PI controller with Ziegler-Nichols tuning,while pH stabilization is achieved through automated injectionof sodium bicarbonate or citric acid solutions. Experimentalresults show that the system successfully maintains watertemperature at 30 °C and pH within the optimal range of 6.8–7.8. Furthermore, growth trials over 14 days indicate that theaquarium with the control system achieved an average SpecificGrowth Rate (SGR) of 2.561%, compared to 1.415% in theuncontrolled group. These results demonstrate that the smartsystem significantly enhances fish growth efficiency byensuring stable environmental parameters and accuratefeeding schedules.Keywords - Smart aquarium, IoT, Snakehead fish